Pengaruh Latihan Pendekatan Taktik terhadap Keterampilan Dribbling Bola pada Siswa Ektrakurikuler Sepakbola di SMA Negeri 4 Purworejo - Juni Isnanto; Al Ilham; Meri Haryani; Nurkhoiroh Nurkhoiroh; Muh. Faisal Lutfi Amri (Departement of Mathematics Education, 2023)
Football extracurricular participants at SMA Negeri 4 Purworejo do not yet have good dribbling skills. This study aims to determine the effect of tactical approach training on the dribbling skills of football extracurricular students at SMA Negeri 4 Purworejo. This research is an experimental research with one group pretest-posttest research design. The population of this study were all students who took part in soccer extracurricular, totaling 16 children. The instrument used in using the dribbling test was from Subagyo Irianto. The data analysis technique used the Kolmogorov-Smirnov test for normality test, homogeneity test and t-test for hypothesis testing, and correlated samples at a significance level of 5%. The test results show that there is an effect of tactical approach training on ball dribbling skills. The hypothesis test shows that the tcount is (4.614) and the p-value (0.000) <0.05, so it shows that there is a significant difference in dribbling skills after being treated with tactical approach exercises. Based on the results, the average (mean) shows the posttest mean < pretest. From these results it can be concluded that there is a significant effect of tactical approach training on the ball dribbling skills of soccer extracurricular students at SMA Negeri 4 Purworejo. Improved ball dribbling skills by 1.52563 or 7.99% (obtained from mean different divided by mean pretest multiplied by 100%).